Studie av effekterna efter behandling mot viltarbete i plantskog i östra Götaland - Tallgren, Elias; Andersson, Henrik (2020)
iv Abstract For many years, the game has been a problem when establishing new forest, which over the years has not become an easier task in traditional forestry. The number of new game species has increased, and the hunters have not been able to keep the populations down. When a newly planted forest is grazed by the game, the quality of the plant deteriorates and a loss of growth occurs, which in turn leads to a downgrading of the log and lower value. The treatments against wild grazing have focused on making the plant less attractive in order for the game to avoid it during a period when the forest is more attractive as a source of food. The purpose of this study was to see if a number of treatments currently available on the market are efficient enough to reduce the grazing in young forest plantations. In southeast Sweden where the study was conducted, different treatments have been used for some time, but with varying results and the question has arisen how well it really works. A field inventory was performed on several different tracts treated with Trico, Arbinol and HaTe2. The inventory of the plants was carried out during the month of April when the most intense grazing period had passed. The inventory on each of the 37 included tracts was carried out as 30 randomly sampled plots for each tract. Within these test plots, information on non-grazed and grazed plants was registered. The result gives an insight that the different treatments had an effect on the amount of grazing. Since the study included a comparison with untreated tracts, a clear pattern could be observed where the percentage of grazed plants was smaller on the treated tracts compared to untreated. The conclusion was that a relatively large difference existed between treated plants and untreated in terms of damage caused by grazing.